Levels of SAT serotype foot and mouth disease viruses in tissues of experimentally infected cattle carcasses and those from the wildlife-livestock interface in the Zambezi Region of Namibia - Thomson, G.R. (Gavin) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.